Converting domestic wastes into renewable source to produce electrical and thermal energy: legal aspects - Кременовська, І. В. (НДІ ПЗІР НАПрН України, 2016)
The paper analyzes the legal aspects of economic activity on the transformation of domestic output at reducing resource for the production of electricity and heat. It is proved that the construction of new incinerators in regions of Ukraine will help address priorities in the direction of environmental security and energy independence.
Keywords: waste; regenerative fuels; recycling; alternative energy sources; відходи; регенеративне паливо; переробка; альтернативні джерела енергії